Ảnh hưởng của sự khuyến khích học tập từ giảng viên đến việc thực hành tự đánh giá của sinh viên: Vai trò điều tiết của môi trường học tập đạo đức - Lê Thị Ngọc , Trâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Self-assessment is an essential skill for students to understand their capacity which then improves their learning process. This study aims to test the effect of academic emphasis on student self-assessment practice, with the moderating role of school ethical climate. Using social cognitive theory to explain the relationship between variables, the study collected 530 responses from college and university students by convenience, non-probability sampling method. The results from PLS-SEM showed that academic emphasis has a positive effect on student self-assessment practice and the school’s ethical climate moderates this relationship.